The Sublime Perversion of Capital : Marxist Theory and the Politics of History in Modern Japan - Walker, Gavin, 1979- (Book collections on Project MUSE., 2016)
In The Sublime Perversion of Capital Gavin Walker examines the Japanese debate about capitalism between the 1920s and 1950s, using it as a ""prehistory"" to consider current problems of uneven economic development and contemporary topics in Marxist theory and historiography.